Implementasi Peraturan Daerah Tentang Pajak Restoran Dan Rumah Makan Pada Kantor Badan Pendapatan Daerah Kabupaten Kolaka Utara - Khumaerah, Ratu; Amir, Muh; Yusuf, Muhammad (Universitas Halu Oleo, 2020)
This study aims to determine how the implementation of local regulations regarding restaurants in north kolaka regency. The method used in this study is a qualitative descriptive research method by means of observation, interviews and documentation. Results of this study indicate that the implementation of local regulations on restaurant and restaurant tax in north kolaka regency has shown that the policy is less effective to implement. The ineffective implementation judging from the realization of the revenue from restaurant tax is far below the determined target. Policy targets in terms if increasing restaurant tax revenue are not in accordance with the realization in the field, starting from not in line with the size and objectives of the policy to the lack of utilization and availability of resources so that several times the target changes from the previous one. This decrease in the amount of income each month signifies the lack of contribution of restaurant tax on local revenue wanted to increase. In addition, this is also judged due to the fact that many people do not agree with the stipulation of this policy so that their participation is less effective.